This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ( f ◦ g )( x ) = f ( g ( x )) ( f ◦ g )( x ) = ( x 32 x ) 2 + 2 1. Given the function g ( t ) = 1 t + t 2 and h(t)=2 t 3 , calculate ( g + h )( t ) = ( gh )(1) = ( gh )( x ) = ( g h ) ( t ) = ± h g ² (2) = ( g ◦ h )( t ) = ( h ◦ g )(1) =...
View
Full
Document
This note was uploaded on 04/14/2008 for the course MATH 138 taught by Professor Hubbard during the Spring '08 term at Stephen F Austin State University.
 Spring '08
 Hubbard
 Algebra, Addition, Subtraction

Click to edit the document details